The Role of Digital Technology in Enhancing Business Productivity in Indonesia: A Study on Bank Rakyat Indonesia - Pertiwi, Rizky Maulani; Indriani, Farida (Research Horizon, 2024)
The acceleration of digital transformation has become a crucial element in adapting to the needs of the times. According to a Deloitte survey, 67% of companies that implement digital transformation have proven to be superior compared to competitors that have not adopted digitalization, especially during the Covid-19 pandemic. As one of the leading banks, BRI is also actively promoting digital transformation. Since setting its vision to become The Most Valuable Banking Group in Southeast Asia & Champion of Financial Inclusion by 2025, BRI has consistently strengthened the digitalization aspect within the company. This research employs a qualitative descriptive approach to provide a comprehensive overview of digital transformation strategies and their impact on the company's competitiveness. The main findings of this study indicate that accelerating digital transformation is essential for helping companies adapt to changes and maintain competitive advantage. This research contributes significantly by highlighting the importance of digital transformation as a key strategy for maintaining competitiveness in the era of technological disruption. Moreover, this study supports strategic decision-making for companies, particularly in the banking and financial sectors like BRI, which focuses on strengthening digitalization as part of its long-term vision. These findings also serve as a guide for business leaders in designing effective digital transformation policies for the future.